Modeling rapid solidification and melting processes for multiphase flows in a welding technology application - Xiong, Xin; Könözsy, László Z. (Miskolc University Press, 2022)
This article presents unsteady simulations of laser welding based on a rapid solidification/melting model using the ANSYS-FLUENT software package with the implementation of a UDF (User Defined Function) C code. It assumes a flat interface of liquid and gas without plasma plume, evaporation and reflection and absorption effect. In the simulations, a variety of parameters are considered with different welding speeds and laser powers. The results show that with the increase of laser power, liquid fraction and velocity, penetration depth and bead width all increase. In contrary, with the increase of welding speed, the temperature, liquid fraction, penetration depth, and bead width all decrease, while the velocity magnitude is an exception. It has also been found that the increase of welding speed distorts the pool shape and forms a long tail in temperature, liquid fraction and velocity contour. The buoyancy force did not have a significant impact on the results, while the convective term makes the velocity, temperature and liquid fraction smaller. Furthermore, the negative Marangoni shear stress makes the velocity along the height and the width direction smaller in the middle of the workpiece and larger on the edges. The simulation results show a similar tendency to that obtained by other authors. The reason for the possible differences is due to the unsteadiness of the fluid flow field and the slightly different boundary conditions imposed in the model presented here. The novelties of this work are unsteady simulations, new boundary conditions and parametric studies relevant to industrial applications.
Keywords: Rapid Solidification/Melting; Laser Welding; Laser Power; Welding Speed; Computational Fluid Dynamics (CFD); Engineering